Inovação no setor público: uma proposta de framework com foco em uma gestão sustentável - Camargo Bisneto, Eduardo Lacerda de (2025)
This Master’s degree thesis investigates innovation in the public sector, proposing an organizational framework focused on ustainable development. The main objective is to structure a model that enhances innovation as a tool for improving public governance, enabling agile and sustainable responses to contemporary systemic challenges. The study is justified by the need to trengthen public sector capacity in the face of global crises, increasing inequalities, and demands for greater efficiency, transparency, and social participation. The central hypothesis is that public sector innovation, when structured holistically and integratively, can overcome historical barriers and foster sustainable management, especially when anchored in pillars such as people/culture, nvironment, information/data, and bureaucracy/processes. The research is grounded in classical and contemporary theoretical frameworks, highlighting authors like Schumpeter and Perez, as well as internationally recognized models such as those from PSI/OECD and NESTA. Methodologically, the study employs a systematic literature review, comparative analysis of international odels, and adaptation of these frameworks to the Brazilian institutional context. The proposed framework aims to integrate ndividual, organizational, and systemic dimensions, identifying critical success factors and barriers to innovation, with the goal of promoting a more innovative, efficient public administration aligned with the Sustainable Development Goals